Tumor suppressor activity and inactivation of galanin receptor type 2 by aberrant promoter methylation in head and neck cancer. Issue 2 (10th October 2013) - Misawa, Yuki; Misawa, Kiyoshi; Kanazawa, Takeharu; Uehara, Takayuki; Endo, Shori; Mochizuki, Daiki; Yamatodani, Takashi; Carey, Thomas E.; Mineta, Hiroyuki
<x xml:space="preserve">Abstract</x> BACKGROUND There is accumulating evidence that galanin receptors (GALRs) may be tumor suppressors in head and neck squamous cell carcinoma (HNSCC). Promoter methylation status and gene expression were assessed in a large panel of head and neck primary tumors, based on the hypothesis that cytosine‐guanine dinucleotide (CpG) hypermethylation might silence the galanin receptor 2 (GALR2) gene. METHODS GALR2 expression was examined in a panel of cell lines by using quantitative reverse transcription polymerase chain reaction (RT‐PCR). The methylation status of the GALR2 promoter was studied using quantitative methylation‐specific PCR (Q‐MSP). UM‐SCC‐1 was stably transfected to express GALR2. RESULTS GALR2 expression was suppressed in UM‐SCC cell lines, whereas nonmalignant cell lines exhibited stable expression. GALR2 methylation found in 31 of 100 (31.0%) tumor specimens was significantly correlated with the methylation status of both GALR1 and Galanin. The observed GALR2 promoter hypermethylation was statistically correlated with a decrease in disease‐free survival (log‐rank test, P = .045). A multivariate logistic‐regression analysis revealed a high odds ratio for recurring methylation of GALR2 and the gene pair GALR2 and Galanin, 8.95 (95% confidence interval, 2.29‐35.03; P = .024) and 9.05 (95% confidence interval, 1.76‐46.50; P = .008), respectively. In addition, exogenous expression of GALR2 suppressed cell proliferation in UM‐SCC‐1 cells with hypermethylated Galanin and GALR2‐proficient cell lines. CONCLUSIONS Frequent promoter hypermethylation in association with prognosis, and growth suppression after re‐expression, supports the hypothesis that GALR2 may act to suppress tumor activity. GALR2 is a potentially significant therapeutic target and prognostic factor for this cancer type. Cancer 2014;120:205–213. © 2013 American Cancer Society.